Hubungan Pembelajaran Berdiferensiasi, Student Well-Being dan Hasil Belajar Matematika Siswa Kelas V MI Negeri 11 Boyolali - Ernawati; Rasimin (Universitas Ngudi Waluyo, 2025)
Abstract Education in the 21st century demands flexible and inclusive approaches to accommodate student diversity, yet uniform teaching methods are often ineffective, particularly in mathematics education. Differentiated instruction, which tailors content, process, and products to students’ needs, offers a solution to enhance student well-being and mathematics learning outcomes. However, many instructional practices still fail to support student well-being. Therefore, this study aims to examine the relationship between differentiated instruction, student well-being, and mathematics learning outcomes among fifth-grade students at MI Negeri 11 Boyolali. This study employs a quantitative correlational approach to investigate the relationship between differentiated instruction as the independent variable and student well-being and mathematics learning outcomes as dependent variables, conducted at MI Negeri 11 Boyolali from May to June 2025. The population consists of fifth-grade students, with a sample of 62 students selected through purposive sampling due to their exposure to differentiated instruction. Data were collected via questionnaires (based on Tomlinson’s model for differentiated instruction and Self-Determination Theory for student well-being), written tests for mathematics learning outcomes, observation of instructional implementation, and documentation of formative test scores. Construct validity was tested using factor analysis (item-total correlation >0.3), reliability with Cronbach’s Alpha (>0.7), and data were analyzed using SPSS version 20 with Kolmogorov-Smirnov normality tests, descriptive analysis (mean, median, standard deviation), and Spearman/Pearson correlation with a significance level of α=0.05. A significant strong positive relationship exists between differentiated instruction and student well-being among fifth-grade students at MI Negeri 11 Boyolali (r=0.639, p<0.001). A significant strong positive relationship exists between differentiated instruction and mathematics learning outcomes (r=0.512, p<0.001). A significant moderate positive relationship exists between student well-being and mathematics learning outcomes (r=0.450, p<0.001). Abstrak Pendidikan abad ke-21 menuntut pendekatan fleksibel dan inklusif untuk mengakomodasi keberagaman siswa, namun pendekatan seragam sering tidak efektif, terutama dalam pembelajaran matematika. Pembelajaran berdiferensiasi, yang menyesuaikan konten, proses, dan produk dengan kebutuhan siswa, menjadi solusi untuk meningkatkan student well-being dan hasil belajar matematika. Namun, banyak pembelajaran masih belum mendukung student well-being. Oleh karena itu, penelitian ini bertujuan mengkaji hubungan pembelajaran berdiferensiasi, student well-being, dan hasil belajar matematika pada siswa kelas V MI Negeri 11 Boyolali. Penelitian ini menggunakan pendekatan kuantitatif korelasional untuk mengkaji hubungan antara pembelajaran berdiferensiasi sebagai variabel independen dengan student well-being dan hasil belajar matematika sebagai variabel dependen, dilakukan di MI Negeri 11 Boyolali pada Mei-Juni 2025. Populasi penelitian adalah siswa kelas V, dengan sampel 62 siswa dipilih melalui purposive sampling.karena telah menerapkan pembelajaran berdiferensiasi. Data dikumpulkan melalui kuesioner (berdasar model Tomlinson untuk pembelajaran berdiferensiasi dan Self-Determination Theory untuk student well-being), tes tertulis untuk hasil belajar matematika, observasi implementasi pembelajaran, dan dokumentasi nilai formatif. Validitas konstruk diuji dengan analisis faktor (korelasi item-total >0,3), reliabilitas dengan Cronbach’s Alpha (>0,7), dan data dianalisis menggunakan SPSS versi 20 dengan uji normalitas Kolmogorov-Smirnov, analisis deskriptif (mean, median, standar deviasi), serta korelasi Spearman/Pearson dengan signifikansi α=0,05. Kesimpulan dari penelitian ini adanya hubungan positif signifikan antara pembelajaran berdiferensiasi dan student well-being (r=0,639, p<0,001), pembelajaran berdiferensiasi dan hasil belajar matematika (r=0,512, p<0,001), serta student well-being dan hasil belajar matematika (r=0,450, p<0,001) pada siswa kelas V MI Negeri 11 Boyolali.